Seismic building design work process using building information modeling (BIM) technology for Malaysian Government projects - Mahamood, Siti Zati Hanani (Emerald Publishing Limited, 2022)
Purpose – This paper aims to improve the seismic building design (SBD) work process for Malaysian Government projects. Design/methodology/approach – Semi-structured interviews were virtually conducted to a small sample size of internal and external stakeholders from the Malaysian Government technical agency. There were seven of them, comprising Structural Engineers, an Architect, a Quantity Surveyor and consultants-linked government projects. The respondents have at least five years of experience in building design and construction. Findings – The paper evaluates the current SBD work process in the government technical agency. There were four main elements that appear to need to be improved, specifically in the design stage: limitations in visualization, variation of works, data management and coordination. Research limitations/implications – This study was limited to Malaysian Government building projects and covered a small sample size. Therefore, further research is recommended to extend to other government agencies or ministries to obtain better results. Furthermore, the findings and proposal for improvements to the SBD work process can also be replicated for other similar disasters resilience projects. Practical implications – The findings and proposal for improvements to the SBD work process can also be replicated for other similar disasters resilience projects. Social implications – This study was limited to government building projects and covered a small sample size. Therefore, further research is recommended to extend to other government agencies or ministries to obtain better results. Furthermore, the findings and proposal for improvements to the SBD work process can also be replicated for other similar disasters resilience projects. Originality/value – This study provides an initial step to introduce the potential of building information modeling for SBD in implementing Malaysian Government projects. It will be beneficial both pre-and post- disaster and is a significant step toward a resilient infrastructure and community.